TIPsy tour guides: how microtubule plus-end tracking proteins (+TIPs) facilitate axon guidance - Bearce, Elizabeth A.; Erdogan, Burcu; Lowery, Laura Anne (Frontiers in Cellular Neuroscience, 2015)
The growth cone is a dynamic cytoskeletal vehicle, which drives the end of a developing axon. It serves to interpret and navigate through the complex landscape and guidance cues of the early nervous system. The growth cone’s distinctive cytoskeletal organization offers a fascinating platform to study how extracellular cues can be translated into mechanical outgrowth and turning behaviors. While many studies of cell motility highlight the importance of actin networks in signaling, adhesion, and propulsion, both seminal and emerging works in the field have highlighted a unique and necessary role for microtubules (MTs) in growth cone navigation. Here, we focus on the role of singular pioneer MTs, which extend into the growth cone periphery and are regulated by a diverse family of microtubule plus-end tracking proteins (+TIPs). These +TIPs accumulate at the dynamic ends of MTs, where they are well-positioned to encounter and respond to key signaling events downstream of guidance receptors, catalyzing immediate changes in microtubule stability and actin cross-talk, that facilitate both axonal outgrowth and turning events.